Efektivitas program magrib mengaji dalam meningkatkan kelancaran membaca al-Qur’an anak di Desa Perkebunan Tanah Gambus Kabupaten Batu Bara - Fikri Maulana; Ihsan Satrya Aazhar (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This article aims to describe the activities of the maghrib recitation program in Tanah Gambus Plantation Village, Batu Bara Regency and to explore information about the ability to read the Koran for children in the village obtained from the maghrib recitation program. This research uses a qualitative method with the type of phenomenological research and uses observation data collection techniques, interviews and documentation. Based on these findings, the maghrib recitation program in Tanah Gambus Plantation Village has a good effect on children's fluency in reading the Koran. Children who study and join the maghrib recitation program are already able to read the Qur'an with the correct tajwid rules, by proving that they have participated in the activities of musabaqah tilawatil qur'an at the sub-district, village and school level and can also become imams Congregational prayers at the Al-Hikmah Mosque. The program formed by BKM Al-Hikmah in 2017 brought changes to the children in the village both in the fluency of reading the Koran and in the ethics and behavior of the children.